51.2k views
1 vote
Select the correct answer Which is the correct simplified form of the expression (4m-2n^8)^1/2 ———— 9m^-6 n^-8

User Promise
by
6.0k points

1 Answer

2 votes

Answer:


= (2m^2n^8)/(3)

Explanation:

Given expression is


((4m^(-2)n^8)/(9m^(-6)n^(-8)) )^{(1)/(2)

The correct simplified form is shown below:-

From the above equation, we will simplify

we will shift
m^(-6) to the numerator and we will use the negative exponent rule, that is


= ((4m^(-2)n^8m^6)/(9n^(-8)) )^{(1)/(2)

now we will shift the
n^(-8) to the numerator and we will use the negative exponent rule, that is


= ((4m^(-2)n^8m^6n^8)/(9) )^{(1)/(2)

here we will solve the above equation which is shown below


= ((4m^4n^(16))/(9)) ^(1)/(2)

So,


= (((2)^2(m^2)^2(n^8)^2)/((3)^2) ^(1)/(2)

Which gives result


= (2m^2n^8)/(3)

User Hsuan Lee
by
5.5k points